Histomorphological and Histochemical Investigation of The Vagina of Adult Guinea Pigs (Cavia porcellus) - Al-Saffar, F. J.; Al-bbadi, Hazim N.H (The Iraqi Journal of Veterinary Medicine, 2020)
This study was carried out to identify the morphological, histological and histochemical features of the vagina of the adult guinea pig (Cavia porcellus). To perform such project, 14 adult guinea pigs at their diestrous period were bought from the local breeders directly. Animals were euthanized, dissected and subsequently specimens from the cranial, middle and caudal portions of the vagina were collected and fixed. Fixation was implemented by using 10% neutral buffered formalin and Bouin’s solution. Post routine processing such as dehydration, clearing, embedding and blocks preparation, tissue sections of 6 μm were prepared and stained by using hematoxylin-eosin, Masson’s Trichrome, Alcian blue and Periodic acid shiff stains. Gross findings revealed that the vagina in the adult guinea pigs was characteristically very long tube-like structure with wide diameter. The vagina entirely was running ventral to the colon and then under the rectum in the pelvic cavity. It was terminated caudally by the vaginal orifice independent to the urethral orifice of the urinary system. Microscopic findings revealed mucous columnar lining epithelium which was folded at the vaginal fornix decreased caudally toward the external vaginal orifice where the epithelium changed into stratified squamous epithelium not keratinized. Thin dense lamina propria was continuous with loose connective tissue of the submucosa. Thickness of tunica muscularis was decreased which was surrounded with thick adventitia. Histochemically, the non-ciliated mucous columnar cells present in the lining epithelium of the cranial and middle regions of the vagina were positively stained with AB (pH 2.5) and PAS stains. The reaction with AB (pH 2.5) was more intense compared to the staining with PAS so that it indicated that mucin was more acidic than neutral in nature. Characteristic conclusions include that the vagina opening was U-shaped not circular and closed by transparent closure during the diestrous period. Histologically, the vagina also lined with mucoid lining and only the orifice and adjacent area lined with stratified squamous epithelium. Moreover, current study recorded differences in both macroscopic and microscopic aspects of the vagina in the guinea pigs compared to other animal considered laboratory species.